Gambaran Personal hygiene dan Tingkat Pengetahuan Dengan Kejadian Keputihan Pada Santri Putri Di Pondok Pesantren Putri Banjarbaru - Nurbidayah; Rasidah; Nafila; Bio Putri Ayanti (Jurnal Analis Kesehatan Kendari, 2026)
Vaginal discharge is a common reproductive health problem among adolescent girls and may be influenced by personal hygiene practices and knowledge of reproductive health. Female students living in Islamic boarding schools are at higher risk due to shared facilities, crowded dormitories, and limited access to health services. This study aimed to describe personal hygiene, level of knowledge, and the incidence of vaginal discharge among female students at Wali Songo Putri Islamic Boarding School, Banjarbaru, in 2026. This research used a descriptive design with a cross-sectional approach. The population consisted of 78 female students, and 55 respondents were selected using purposive sampling based on inclusion and exclusion criteria. Data were collected using a closed-ended questionnaire that had been tested for validity and reliability. The data were analyzed using univariate analysis and presented in frequency distribution tables. The results showed that most respondents had good personal hygiene, with 26 students (47.3%), followed by moderate personal hygiene with 21 students (38.2%) and poor personal hygiene with 8 students (14.5%). The level of knowledge about vaginal discharge was mostly good, with 24 students (43.6%), followed by moderate knowledge with 21 students (38.2%) and poor knowledge with 10 students (18.2%). The incidence of vaginal discharge showed that 48 students (87.3%) experienced pathological vaginal discharge, 6 students (10.9%) experienced physiological vaginal discharge, and 1 student (1.8%) did not experience vaginal discharge. In conclusion, most female students had good personal hygiene and good knowledge; however, the incidence of pathological vaginal discharge remained high. Therefore, reproductive health education, improvement of sanitation facilities, and early health screening are needed to prevent pathological vaginal discharge among female students.